Brand valued : how socially valued brands hold the key to a sustainable future and business success - Champniss, Guy.; Rodes Vila, Fernando (Hoboken, NJ : John Wiley & Sons, 2011)
'New techniques to refresh and recharge your brands. How do you establish and maintain a strong long-term relationship between your brand and your consumers? Successful brand managers know that it is all about trust and keeping the consumers engaged.The success of recent'green' campaigns as a means of connecting with, satisfying, and attracting new consumers is just the tip of the iceberg. As the international playing field continues to be leveled, in order to sustain and expand their success, brand owners must interact with their customers more than ever before, forging new and stronger links, and increasing their stock of social capital.At last, there is a book that addresses the growing significance of social capital in the business world. Brand Valued explores how as the strength, depth, and quality of interactions between a brand and its customers improve, increased opportunities to demonstrate trustworthiness arise. This in turn creates a self-fulfilling cycle, wherein trust begets social capital, which begets more trust--and even shared thinking--not to mention better sales. Brand Valued will receive the full support of Havas, the fifth largest global communication and marketing services group in the world. In easy to understand terms, and using concrete examples, Brand Valued provides: The tools necessary to stimulate dialogue--and new ways of thinking--between a brand and its intended audience; Methods for extending brand messaging to wider audiences; Ideas on how to make brands the engines of social capital, getting rid of unsustainable practices to foster more sustainable patterns of consumer behaviour; Suggestions for the development of a new brand strategy that reduces costs through innovative and lasting solutions to problems; Unpublished data on the role of consumer trust in new products based on research carried out by the Havas Group across over 150 brands in nine different markets; A wiki component to the book in an accompanying website. Designed to forge stronger channels of dialogue and communication with customers and consumers, the book is a must-read for anyone committed to keeping their brand relevant in the twenty-first century'--
Includes bibliographical references and index.
Keywords: Branding (Marketing) -- Social aspects; Social responsibility of business; BUSINESS & ECONOMICS / General